FORMULASI ASAS KERAHASIAAN INTELIJEN KEJAKSAAN DALAM PENYELENGGARAAN FUNGSI INTELIJEN PENEGAKAN HUKUM - Sukawinata, I Gusti Ngurah Anom; Aryana, I Wayan Putu Sucana; Laksmi Dewi, Cokorde Istri Dian (VYAVAHARA DUTA, 2024)
The principle of confidentiality is a very important basic principle for prosecutorial intelligence in maintaining the implementation of intelligence activities. This research aims to examine and analyze the formulation of the Prosecutor's Intelligence Confidentiality Principle in the Implementation of Law Enforcement Intelligence Functions and the Legal Consequences of Leaks of Intelligence Secrets During the Retention Period. This research is normative legal research, and the approaches used are the statutory and legal concept approach. The sources of legal materials used are primary and secondary sources. The formulation of the principle of confidentiality of prosecutorial intelligence in the implementation of law enforcement intelligence functions is regulated in the form of law, namely Law of the Republic of Indonesia Number 17 of 2011 concerning State Intelligence as a legal umbrella for intelligence functions in the law enforcement system and Law of the Republic of Indonesia Number 11 of 2021 concerning Amendments to Law of the Republic of Indonesia Number 16 of 2004 concerning the Prosecutor's Office. The legal consequences of leaking secret intelligence during the retention period are in the form of criminal liability, specifically if the prosecutor's intelligence personnel leaks efforts, work, activities, targets, information, special facilities, special tools and equipment, support, and/or State Intelligence Personnel related to the implementation of functions and activities of State Intelligence, there is a criminal penalty plus 1/3 (one third) of each maximum criminal threat if carried out in a state of war. Moreover, these personnel receive code of ethics sanctions from the prosecutor's office.